The psychological consequences of living with coronary heart disease: Are patients' psychological needs served? A mixed‐method study in Germany. (21st October 2022) - Peltzer, Samia; Köstler, Ursula; Müller, Hendrik; Scholten, Nadine; Schulz‐Nieswandt, Frank; Jessen, Frank; Albus, Christian; ,
Abstract: Introduction: This mixed‐method study explores psychological needs, access and barriers in coronary heart disease (CHD) patients with and without mental health issues (MHI) within the German healthcare system. Methods: This study was conducted in three different healthcare settings: two hospitals, two rehabilitation clinics and three cardiology practices in Cologne, Germany. Patients were screened for angiographically documented CHD and other inclusion criteria. In total, 364 CHD patients took part in this study. It consisted of two parts: In the first part, participants filled in a newly developed questionnaire about their psychological needs, access and barriers within the healthcare system and their contact with their doctor in these matters. Then, patients were screened for MHIs with the help of the Hospital Anxiety and Depression Scale (HADS). When a score above seven was scored on the HADS, patients were additionally screened for specific MHIs using the Structured Clinical Interview for DSM‐IV Axis I Disorders. In the second part, 20 participants were subsequently interviewed in a semi‐structured interview to generate more in‐depth findings. Results: The interviews show that CHD patients with and without MHI experienced a cardiac event as life‐changing and had an urgent need to talk about CHD with their doctor, mostly the general practitioner (GP). When the GP spoke to the patient shortly after the cardiac event, patients experienced relief and were better able to cope with their illness. Only 9.1% reported being aided in their search for psychotherapeutic treatment or drug treatment (4.1%). Conclusion: The needs of CHD patients with and without MHI were not adequately satisfied within our sample. Psychological measures are necessary for sufficient improvement, such as training of doctors in doctor–patient communication (e.g., better support in coping with MHI/CHD), improvements in the procedure (more time for conversations during doctor contacts), and improvement of structural requirements (referring patients faster to psychotherapists). Patient or Public Contribution: We received input from patients during pretests and used the feedback to tailor our questionnaire and the interview guidelines. Afterwards, we disseminated the main results for the patient and public involvement (e.g., public lectures, leaflets for self‐help groups, etc.).